(untitled) (Journal of Mechanical Engineering, 2013)
Transonic flow over a supercritical airfoil leads to the appearances of unsteady shock waves in theflow field. At certain flow conditions, the interaction of unsteady shock waves with boundary layer becomescomplex and generates self-excited shock oscillation, lift fluctuation and thus initiate the buffet. In the presentstudy, Reynolds averaged Navier-Stokes equations with k-? SST turbulence model has been applied to predictthe shock induced buffet onset for the flow over a supercritical airfoil NASA SC(2) 0714. The free streamtransonic Mach number is kept in the range of 0.71 to 0.75 while the angle of attack is varied in a wide range.The onset of buffet is confirmed by the fluctuating aerodynamic properties such as lift-coefficient, pressurecoefficient, static pressure and so on. The self-excited shock oscillation and the corresponding buffet frequencyare numerically analyzed. DOI: http://dx.doi.org/10.3329/jme.v43i1.15782